Importância da orientação educacional no processo educativo - Grinspun, Mirian Paura Sabrosa Zippin (1976)
This dissertation on the importance of Educational Guidance in Education had as its objective the ana1ysis of the fundamental aspects of guidance in order to justify the major assumption of the work. The problem of our study is related to two fundamental aspects: 1 - Educational Guidance as an integrated part of the Educational process; 2 - Vocational guidance as part of Educational Guidance. The research methodology followed a critical and descriptive approach of the data collected in the review of literature. The review of literature was treated in depth with the intention both to collect data for this work and to allow for useful information for guidance Counsellors. The choice of topics based on the hypothesis is particularly related to the importance given to them by the various authors, as well as to our own professional experience. The starting point of the study was the historical development of Educational Guidance. In order to stress the importance of a theoretical basis for the work of the Guidance Counsellor we selected for analysis the theoretical approaches wich have mostly influenced studies in this field. We also sought to show the importance of the Educational Guidance from the point of view of Law 5692/71, which made Guidance compulsory in al1 primary and secondary schools. The 'praxis' of Educational Guidance or the application of theory was analyzed in relationship to the Educational Guidance Services. In this respect, data which could explain the situation of the Services in Rio de Janeiro were brought together as an illustration. It is important to stress the number of Guidance Counsellors is far from being sufficient for the satisfactory development of the objectives of the Law itself. An integrated view of Guidance was suggested in this dissertation as a means for meeting the objectives of Guidance because they seem to us be particularly relevant. Therefore, in order to satisfy both the recommendation of the Law and the needs of the school, it is imperative that Educational Guidance should develop in the direction of an integrated Educational, this position being fundamental to the efficacy of the Educational Process.